1992
DOI: 10.1073/pnas.89.6.2429
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of a protein: selection of potent neutrophil elastase inhibitors displayed on M13 fusion phage.

Abstract: Inhibitors of human neutrophil elastase were engineered by designing and producing a library of phagedisplayed protease inhibitory domains derived from wild-type bovine pancreatic trypsin inhibitor and fractionating the library for binding to the target protease. The affinity of one of the engineered variants for human neutrophil elastase (Kd =

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
74
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(78 citation statements)
references
References 26 publications
3
74
0
1
Order By: Relevance
“…EPI-hNE4 (DX-890) is a low molecular mass (6237 Da) inhibitor of HNE that was discovered and patented by Dyax Corp (Cambridge, MA). It was engineered using phage display (Roberts et al, 1992) and is expressed in Pichia pastoris. It is derived from the second Kü nitz domain of the light chain (bikunin) of the naturally occurring human protease inhibitor, inter-␣-trypsin inhibitor (residues 285-340; Swiss-Prot accession number PO2760), from which it differs at five positions (Becher et al, 2006).…”
mentioning
confidence: 99%
“…EPI-hNE4 (DX-890) is a low molecular mass (6237 Da) inhibitor of HNE that was discovered and patented by Dyax Corp (Cambridge, MA). It was engineered using phage display (Roberts et al, 1992) and is expressed in Pichia pastoris. It is derived from the second Kü nitz domain of the light chain (bikunin) of the naturally occurring human protease inhibitor, inter-␣-trypsin inhibitor (residues 285-340; Swiss-Prot accession number PO2760), from which it differs at five positions (Becher et al, 2006).…”
mentioning
confidence: 99%
“…So far, several studies have shown that through semisynthetic (14,15) or recombinant approaches (16 -18) it is possible to change or enhance the BPTI inhibition spectrum. Additionally, phage display technology has been applied to generate potent inhibitors directed toward different serine proteinases based on either the BPTI sequence (19) or sequences of homologous inhibitors: amyloid ␤-protein precursor (20 -22) and the first domain of TFPI (23,24). Stassen et al converted BPTI into a potent inhibitor of factors VII a -TF, X a , XI a and plasma kallikrein through grafting into BPTI binding loop sequences of individual TFPI domains (17).…”
mentioning
confidence: 99%
“…In comparison, the presence of Ala 39 and Phe 60 in FVIIa resulted in the selection of Ile at the P 3 Ј position, whereas in human leukocyte elastase, Phe was selected to fit in the area flanked by Gly 39 and Ala 60 (14,15,28). At the P 2 Ј position (residue 17), the preference for Ala at position 17 is consistent with a relatively small hydrophobic pocket, which likely involves Ile 151 in plasma kallikrein.…”
mentioning
confidence: 99%